THE IMPACT OF CREATING SHARED VALUE ON PURCHASE INTENTION AND RECOMMENDATION INTENTION: A STUDY IN VIETNAM - Ha Thu Nguyen; Phong Lam Le (Tạp chí Khoa học Đại học Đà Lạt)
Creating shared value (CSV) has been predicted as the next evolution of corporate social responsibility. Companies that follow the CSV approach integrate economic, societal, and environmental objectives in their strategy to pursue sustainability and competitive advantages. This study investigates the effects of CSV contributions (which are framed as economic, social, and environmental contributions) on brand attitude, and then the effects of brand attitude on consumer purchase and recommendation intentions. This research also examines the moderating role of perceived personal relevance on the relationships between economic, social, and environmental contributions and brand attitude. The proposed model was empirically tested on a sample of 234 consumers in a metropolitan city in Vietnam. The results confirm that positive links exist between the three CSV contributions and brand attitude as well as between brand attitude and consumer intentions of purchasing and recommending. The study also finds that perceived personal relevance moderates the effect of environmental contribution on brand attitude. These effects help us better understand previous findings in the literature regarding the influence of CSV on consumer intentions and enrich the limited CSV research. Moreover, this study also provides managerial suggestions for companies in making their CSV decisions.